The role of Iraqi economic performance in explaining market value of shares - Aqeel Shakir A, Salim Sallal R., (Opción, 2019)
The study used many statistical methods as Kolmogorov – Smirnov Test, as well as Simple and Multi Regression to investigate the role of Iraqi economic performance in explaining market value of shares. As a result, the significant statistical of all study independent variables during the 4-year study period on the dependent variable is the market value of the sample companies. In conclusion, the high real value of assets such as real estate and securities due to the low purchasing power coming from the high inflation rates affecting the purchasing power of the local currency.